Jamaica Making The Theresa Roberts Art Collection - Roberts, Emma (Liverpool University Press, 2022)
This book accompanies the first exhibition entirely of Jamaican art to take place in the north-west of the UK. The exhibition, Jamaica Making: The Theresa Roberts Art Collection, is sited at the Victoria Gallery and Museum, Liverpool in 2022, and is a comprehensive presentation of the best of Jamaican art since the 1960s. The Theresa Roberts Art Collection is the private collection of Theresa Roberts, a Jamaican-born businesswoman and philanthropist, who has made the UK her home. This collection offers an important insight into the development of Jamaican art since the country gained independence in 1962. Indeed, the exhibition also acts to commemorate the 60th anniversary of Jamaican independence in 2022. Included in the book are the following: an official welcome from the Prime Minister of Jamaica; an essay by the collector, exhibition donor and philanthropist, Theresa Roberts; an introduction by eminent British-Jamaican art historian, Edward Lucie-Smith; essays by Emma Roberts, the exhibition curator (Liverpool John Moores University), Davinia Gregory-Kameka, writer, educator and researcher (Columbia University, USA) and Sireita Mullings, arts practitioner and visual sociologist (University of Bedfordshire). The final section of the book is the full visual catalogue of the Jamaica Making exhibition - a unique record of this historic exhibition.